KONDISI TANAH DALAM KAWASAN MANGROVE DI DESA NUSAPATI KABUPATEN MEMPAWAH KALIMANTAN BARAT - Dewi, Srinita Kusuma; Herawatiningsih, Ratna (Universitas Tanjungpura, 2017)
Mangrove forests have characteristics that are often flooded by sea water so they have high salinity levels. With this condotion, the mangrove adapts to the salinity of sea water. This research aims to assess the soil condition in the area of mangrove forests, especially in Nusapati Village Mempawah Regency. The research method used in the study is survey method by taking soil samples through purposive sampling. the soil sample was taken at three zones namely the front, middle and rear zones using the sample rings. A laboratory analysis was then performed with a descriptive analysis method. The results of the research showed that the soil condition of the mangrove forest area, especially in Nusapati Village Mempawah Regency in terms of soil texture with sand fraction between (0.17% -1.34%), dust between (42.01% -45.05%), and clay between (54.19% -56.56%) the average texture class has loamy clay fraction. Soil acidity or pH is between (4.44 to 7.59) categorized as acid, very acid, alkaline and neutral. C-Organic values of soil range from high to very high (3.99% -5.05%). CEC values of soil categorized as high to very high namely 22.61 (cmol(+)kg-1) - 28.64 (cmol(+)kg-1). While soil salinity ranges from between 0.66 ppt - 2.95 ppt. Keywords: Mangrove area, Nusapati Village, Salinity, Soil condition